Quantum Chemical Study on the Antioxidation Mechanism of Piceatannol and Isorhapontigenin toward Hydroxyl and Hydroperoxyl Radicals - Lu, Yang; Wang, AiHua; Shi, Peng; Zhang, Hui; Li, ZeSheng (PLOS ONE, 2015)
A systematic study of the antioxidation mechanisms behind hydroxyl (•OH) and hydroperoxyl (•OOH) radical scavenging activity of piceatannol (PIC) and isorhapontigenin (ISO) was carried out using density functional theory (DFT) method. Two reaction mechanisms, abstraction (ABS) and radical adduct formation (RAF), were discussed. A total of 24 reaction pathways of scavenging •OH and •OOH with PIC and ISO were investigated in the gas phase and solution. The thermodynamic and kinetic properties of all pathways were calculated. Based on these results, we evaluated the antioxidant activity of every active site of PIC and ISO and compared the abilities of PIC and ISO to scavenge radicals. According to our results, PIC and ISO may act as effective •OH and •OOH scavengers in organism. A4-hydroxyl group is a very important active site for PIC and ISO to scavenge radicals. The introducing of -OH or -OCH3 group to the ortho-position of A4-hydroxyl group would increase its antioxidant activity. Meanwhile, the conformational effect was researched, the results suggest that the presence and pattern of intramolecular hydrogen bond (IHB) are considerable in determining the antioxidant activity of PIC and ISO.